1992
DOI: 10.1029/92gl00240
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐hemispheric Transport of Volcanic Ash from a 1259 A.D. Volcanic Eruption to the Greenland and Antarctic Ice Sheets

Abstract: A strong volcanic sulfuric acid signal corresponding to an age of 1259 A.D. has been reported in ice cores from Greenland, Antarctica, and Arctic Canada. Tiny (< 5 μm) volcanic glass shards were reported previously in samples from this layer in an ice core from the South Pole. Here we report the discovery of volcanic glass shards from a contemporaneous layer in an ice core from Summit, Greenland. The major element composition of the glass shards in the Greenland sample are identical to those from the South Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 17 publications
3
64
0
Order By: Relevance
“…These processes also modulate the production of 14 C, such that there are irregularly spaced features that are common in records of 14 C and 10 Be (Beer and others, 1988;Finkel and Nishiizumi, 1997). Features in the 10 Be record in the Siple Dome core must occur before the features occur in 14 C dendrochronology records, because of time lags in the carbon cycle (Siegenthaler and Beer, 1988). At GISP2 we observed this offset to be about 20 years, which is consistent with our understanding of the carbon cycle.…”
Section: Available Datasetssupporting
confidence: 75%
“…These processes also modulate the production of 14 C, such that there are irregularly spaced features that are common in records of 14 C and 10 Be (Beer and others, 1988;Finkel and Nishiizumi, 1997). Features in the 10 Be record in the Siple Dome core must occur before the features occur in 14 C dendrochronology records, because of time lags in the carbon cycle (Siegenthaler and Beer, 1988). At GISP2 we observed this offset to be about 20 years, which is consistent with our understanding of the carbon cycle.…”
Section: Available Datasetssupporting
confidence: 75%
“…1) after the probably largest explosive eruption of the past few thousand years. The source volcano of this event is still unknown, although bipolar sulfate deposition together with its consistent chemical signature (43) at around Ϸ1258 AD makes it clear that it is a tropical event. This particularly large event was followed by a remarkable sequence of large eruptions, causing a clear temperature decrease of several tenths of a degree Celsius over the late 13th century (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The source of this vapour could be mafic composition magma intruded into the lower parts of the chamber, which is not subsequently erupted but which, over centuries or millennia, has contributed its complement of volatiles to the overlying magma (see Wallace (2001) for a penetrating account of the origins, extent and time scales of pre-eruptive exsolved volatiles in magmas). Following this reasoning, Palais et al (1992) suggested that the mystery eruption could have taken place at El Chichón volcano in Mexico, known for its high-sulphur yield explosive eruptions in March-April 1982. They highlighted a tephra sequence radiocarbon dated at <625 ± 75 years BP by Tilling et al (1984), and described by the latter authors as 'several times' larger than the 1982 eruptions (whose total magnitude was about 3 × 10 12 kg according to Carey and Sigurdsson (1989)).…”
Section: Characteristics Of the Mystery Eruptionmentioning
confidence: 99%